2015
DOI: 10.3390/rel6041346
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Perceptions of Spirituality and Spiritual Care in Different Health Care Settings in the Netherlands

Abstract: This paper shows similarities and differences in perceptions and competences regarding spirituality and spiritual care of nurses in different health care settings. Research on this specific topic is limited and can contribute towards a nuanced implementation of spiritual care in different nursing care settings. Four hundred forty nine nurses in different health care settings completed a questionnaire concerning spirituality and spiritual care, spiritual care competence, and personal spirituality. Respondents r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
56
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 27 publications
10
56
3
2
Order By: Relevance
“…Many participants expressed confusion regarding the place of personal spiritual or religious tendencies and beliefs in the professional workspace. Others have noted this trend and attributed it to the increasing secularisation of society (van Leeuwen and Schep-Akkerman 2015;McSherry and Jamieson 2013). Generating a supportive environment in which appropriate expression of spirituality and/or religiosity by nursing staff will likely improve work satisfaction, patient care and protect against psycho-physical exhaustion or 'burn out' (Taylor 2014).…”
Section: Supporting Staff and Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many participants expressed confusion regarding the place of personal spiritual or religious tendencies and beliefs in the professional workspace. Others have noted this trend and attributed it to the increasing secularisation of society (van Leeuwen and Schep-Akkerman 2015;McSherry and Jamieson 2013). Generating a supportive environment in which appropriate expression of spirituality and/or religiosity by nursing staff will likely improve work satisfaction, patient care and protect against psycho-physical exhaustion or 'burn out' (Taylor 2014).…”
Section: Supporting Staff and Patientsmentioning
confidence: 99%
“…The spirituality and nursing literature has grown considerably in the last decade in such areas as nurse education (Wu et al 2016;Ross et al 2016;Timmins et al 2015;Baldacchino 2011), communication (Wittenberg et al 2016), nurse's self-care (Spadoni and Sevean 2016), experiences in the clinic (Nascimento et al 2016;Cone and Giske 2016;van Leeuwen and Schep-Akkerman 2015), assessment (McSherry and Ross 2002;Adib-Hajbaghery and Zehtabchi 2016) and definitions (Tanyi 2002;Reinert and Koenig 2013). The research, exemplified by recent spirituality and cancer meta-analysis Sherman et al 2015;Salsman et al 2015) confirms the importance of attending to this domain, is such that the Scottish National Health Service (NHS Education Scotland 2009), the US Joint Commission on Accreditation of Healthcare Organisations (Joint Commission on Accreditation of Healthcare Associations 2005), and New Zealand's Ministry of Health (Ministry of Health 2010) all call for spiritual needs to be addressed in various healthcare settings.…”
Section: Introductionmentioning
confidence: 99%
“…It has been emphasized in studies in this country and abroad that a lack of education is an important factor among the reasons for nurses not meeting the spiritual needs of individuals [5,8,16,17]. Also, McSherry reported that the concept of spirituality and spiritual care in nursing remained theoretical in the fields of organization, management and practice, and that going beyond this is necessary [18].…”
Section: Introductionmentioning
confidence: 99%
“…These authors also emphasised the importance of reflection for the development of spiritual competence [4]. In van Leeuwen and Schep-Akkerman's [28] study, nurses (n = 449) self-declared themselves spiritually competent, with mental health nurses receiving higher scores. In another paper in this series [32] most South African nurses (n = 280) determined that spiritual care giving was part of the nurse's role, but need greater preparedness.…”
Section: Educational Aspects and Competencies For Spiritual Carementioning
confidence: 99%
“…Within this list of competencies the importance of assessing and documenting spiritual care needs and interventions are highlighted, but so also is handling one's own beliefs, which can be developed by personal critical reflection. Van Leeuwen, co-authored another of the papers in this Special Issue which specifically addresses spiritual competence of nurses [28]. Spadoni and Sevean [4] also describe an ambitious and detailed education package provided to nursing students, and are convinced of the benefit of and need for such education among nurses, a belief that is reiterated throughout the nursing literature [29][30][31].…”
Section: Educational Aspects and Competencies For Spiritual Carementioning
confidence: 99%